2019
DOI: 10.1021/acs.biochem.9b00714
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Enzyme Production and Structure-Based Discovery Platform for BACE1 Inhibitors

Abstract: BACE1 (Beta-site Amyloid Precursor Protein (APP) Cleaving Enzyme 1) is a promising therapeutic target for Alzheimer’s Disease (AD). However, efficient expression, purification, and crystallization systems are not well described or detailed in the literature nor are approaches for treatment of enzyme kinetic data for potent inhibitors well described. We therefore developed a platform for expression and purification of BACE1, including protein refolding from E.coli inclusion bodies, in addition to optimizing a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…K i values, with the exception of MERS 3CL pro , were obtained by fitting the data to the Morrison equation (Eq. ( 1 )) for competitive inhibition 48 . For these fits, the V max was initially set to a value less than 1.2, the UIVT3 substrate concentration was fixed at 2 μM, and the K m value was fixed at a value of 250 μM.…”
Section: Methodsmentioning
confidence: 99%
“…K i values, with the exception of MERS 3CL pro , were obtained by fitting the data to the Morrison equation (Eq. ( 1 )) for competitive inhibition 48 . For these fits, the V max was initially set to a value less than 1.2, the UIVT3 substrate concentration was fixed at 2 μM, and the K m value was fixed at a value of 250 μM.…”
Section: Methodsmentioning
confidence: 99%
“…Initial velocities were calculated by dividing the observed velocity in the absence of inhibitor (V o ) by the initial velocity at different inhibitor concentrations (V i ). K i values, with the exception of MERS 3CLpro, were obtained by fitting the data to the Morrison equation (Equation 1) for tight-binding inhibitors 45 . …”
Section: Methodsmentioning
confidence: 99%
“…Recently, macro-cyclic ligand bound structures of BACE1 were reported by Yen et al 88 (PDB IDs: 6NV7, 6NV9, 6NW3). The authors further reported experimental K i and K d values as well as several thermodynamic parameters (DH, TDS, and DG) of ligand binding (thermodynamic parameters were calculated using isothermal titration calorimetry (ITC) experiments).…”
Section: Challenge To the Simulation Communitymentioning
confidence: 99%